Potensi Cuka Apel terhadap Waktu Kematian Caplak (Rcichepalus Sanguenus) pada Anjing - Affan Zufar; Bayu Febram Prasetyo; Upik Kesumawati Hadi (Jurnal Health Sains, 2021)
Apple cider vinegar is widely discussed today in addition to having many benefits for body health and facial treatments, this preparation also has antiparasitic properties, especially to repel ticks on dogs. This study aims to analyze the effect of apple vinegjzsar administration on the time of tick death (Rhipicephalus sanguineus). The sample in this study used 50 ticks divided into 5 ticks for 5 treatment groups (K-, 10% Apple Vinegar, 15% Apple Vinegar, 20% Apple Vinegar, K +) with two repetitions. In negative controls using aquades, no tick deaths were found. At the Apple Vinegar concentration of 10% there were 8 tick deaths with an average death at 2 hours 50 minutes after administering the preparations At the Apple Vinegar concentration 15% there were 10 tick deaths with an average death at 2 hours 47 minutes after administration of the preparations. At the Apple Vinegar concentration of 20% there were 10 tick deaths with an average death at 1 hour 15 minutes after administration of the preparation. In the positive control using fipronil 3% with the trademark Deticks there was an average of 5 ticks mortality. The results of this study concluded that Apple Vinegar is very effective as an anti-tick with a minimum concentration of 20% can kill ticks quickly. In addition, it was also found that Apple Vinegar with a concentration of 20% was more effective at killing ticks than fipronil 3%.